2007
DOI: 10.1007/s11010-007-9589-0
|View full text |Cite
|
Sign up to set email alerts
|

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells

Abstract: Since Notch signaling plays a critical role in stem cells and oncogenesis, we hypothesized that Notch signaling might play roles in cancer stem cells and cancer cells with a stem cell phenotype. In this study, we accessed potential functions of the Notch pathway in the formation of cancer stem cells using human glioma. Using RT-PCR, we found that most human astrogliomas of different grades expressed moderate to high level of Notch receptors and ligands. mRNA of Hes5 but not Hes1, both of which are major downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 24 publications
6
93
1
Order By: Relevance
“…5 In a similar way to neural precursor cell culture, those glioma stem-like cells expressing CD133 can be enriched in serum-free medium supplemented with growth factors, in which a fraction of glioma cells continue to proliferate and form spheres instead of monolayer. 10,29 Here, we also cultured U87 and U373 glioma cells in sphere forming conditions (Supplementary Figure S1A) as described before 34,35 and found the increase of CD133, Nestin-expressing cells, compared with monolayer-cultured cells (Figure 1b and Supplementary Figure S1B). Sphere-cultured glioma cells also enhanced mRNA and protein expression of neural stem cell markers such as CD133, Nestin and Musashi-1, compared with monolayer-cultured glioma cells (Supplementary Figure S1B).…”
Section: Inhibitionsupporting
confidence: 52%
See 2 more Smart Citations
“…5 In a similar way to neural precursor cell culture, those glioma stem-like cells expressing CD133 can be enriched in serum-free medium supplemented with growth factors, in which a fraction of glioma cells continue to proliferate and form spheres instead of monolayer. 10,29 Here, we also cultured U87 and U373 glioma cells in sphere forming conditions (Supplementary Figure S1A) as described before 34,35 and found the increase of CD133, Nestin-expressing cells, compared with monolayer-cultured cells (Figure 1b and Supplementary Figure S1B). Sphere-cultured glioma cells also enhanced mRNA and protein expression of neural stem cell markers such as CD133, Nestin and Musashi-1, compared with monolayer-cultured glioma cells (Supplementary Figure S1B).…”
Section: Inhibitionsupporting
confidence: 52%
“…Inhibition of Notch pathway exhausts CD133 þ stem-like tumor cells and suppresses sphere formation in vitro and tumor formation in vivo. 29,33,48 Furthermore, Notch signaling pathway directly upregulates the stem cell marker Nestin in glioma. 49 Consistent with these previous studies, our findings show that Notch-2 expression is upregulated in spherecultured cells, compared with monolayer-cultured cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notch signaling is a critical developmental pathway that controls neural stem cell fate and suppresses radial glia differentiation (Ehebauer et al, 2006). The notch signaling pathway is constitutively active in many high-grade gliomas and has been associated with progression of gliomas (Hulleman et al, 2009;Jeon et al, 2008;Shih and Holland, 2006;Zhang et al, 2008). Notch signaling from endothelial cells to hematopoetic stem cells (HSC) via expression of Notch ligands has been shown to drive the self-renewal characteristics and in vivo repopulation of long-term HSCs that lie adjacent to the vasculature (Butler et al, 2010).…”
Section: Brain Tumor-cell Endothelial-cell Signalingmentioning
confidence: 99%
“…Increased activation of the NOTCH signaling has been reported in several tumor types (18). Recent studies showed that this pathway induces the survival and/or proliferation in GBM and glioma cells (19)(20)(21)(22), and the expression of stem cell markers in glioma cells (21,22). According to these findings, the inhibition of this pathway leads to depletion of stem-like cells and to the block of the engraftment in embryonal brain tumors (23).…”
Section: Introductionmentioning
confidence: 96%